Online Learning Motivation and Satisfaction: A Case Study of Undergraduates vs Postgraduates - Rahmat, Noor Hanim; Sukimin, Ira Syaqira; Sim, Mok Soon; Anuar, Mazura; Mohandas, Eliyas S (International Journal of Asian Social Science, 2021)
The pandemic has accelerated the need for online learning. Educators in schools and institutions of higher learning have no choice but to improvise their teaching methods using online platforms. Instructors assumed learners assumed adapted well with online learning as classes have been going on well. Assignments and tests are all properly done as planned. However, learners attending online classes have mixed reactions over the effectiveness of their learning vial online applications. The motivation model (Keller, 1979) sates four main factors for learners’ satisfaction in learning; attention, relevance, confidence and finally satisfaction. The purpose of this qualitative study is to investigate the perceived online learning motivation and satisfaction among both undergraduate and postgraduate students. The instrument used is an open-ended questionnaire and contains questions pertaining to life commitment, peer communication, module support, confidence, approach to learning. 34 participants responded to the open-ended questionnaires. Findings revealed that learners perceived some factors caused them to be less satisfied with online learning, while some factors are perceived as giving positive online experience.